Priorities and barriers for urban ecosystem service provision: A comparison of stakeholder perspectives from three cities - Buffam, Ishi; Hagemann, Frederik Aagaard; Emilsson, Tobias; Gamstetter, David; Pálsdóttir, Anna María; Randrup, Thomas Barfoed; Yeshitela, Kumelachew; Ode Sang, Åsa (Frontiers in sustainable cities, 2022)
Urban Green Infrastructure (UGI) can provide many needed ecosystem services (ES) to help address challenges like biodiversity loss and climate change while contributing to the health and wellbeing of urban inhabitants. In order to optimize UGI for a given city, a first step is to assess the local ES needs and the potential barriers to ES provision. However, it is not known how consistent these needs and barriers are among cities in different settings. To help address this knowledge gap, the aim of this study was to assess ES priorities and existing barriers to ES provision for three cities varying in socioeconomic, cultural and climatic setting: Addis Ababa (Ethiopia), Cincinnati (USA) and Malmö (Sweden). In case studies of each of the three cities, we carried out workshops with key stakeholders and collected their assessments of both current provision of ES from UGI and future priorities. The workshops were followed by expert stakeholder interviews aimed at highlighting existing barriers to ES provision. In spite of the different urban contexts, expressed ES priorities were similar among the cities, with the highest cross-cutting priorities being climate change adaptation, stormwater runoff management and water quality, mental and physical health, biodiversity, and provision of local food. Stakeholder-expressed barriers to ES provision were also broadly similar among cities, falling into three main categories: structural pressures, gaps in governance, and lack of ecological awareness and vision. Our results suggest that certain key ES priorities and barriers may apply broadly to cities regardless of climatic or socio-cultural context. These generic needs can help direct the focus of future studies, and imply a clear benefit to international, even cross-continental study and knowledge-exchange among practitioners and researchers working with UGI.